Geologic evolution of the eastern Eridania basin: Implications for aqueous processes in the southern highlands of Mars. Issue 11 (20th November 2015) - Adeli, Solmaz; Hauber, Ernst; Le Deit, Laetitia; Jaumann, Ralf
Abstract: The Terra Sirenum region of Mars is thought to have hosted the Eridania paleolake during the Late Noachian/Early Hesperian, and it offers an insight into the regional aqueous history of Mars. We focus on four basins, including Atlantis, Simois, Caralis, and an unnamed basin. They are hypothesized to have hosted isolated lakes after the drainage of the Eridania Lake. We produced a geologic map and derived model absolute ages of our main mapped units. The map and model ages enable us to interpret the geologic history of the region. The basin floors are covered by light‐toned materials containing Fe/Mg‐phyllosilicates. Across most of the region, the Electris unit covers the highlands and is eroded into mesas. The deposition of this unit corresponds to air fall and/or fluvial mechanisms that transported the material into the basins and accumulated it on the plateaus and basin floors and rims. The deposits on the basin floors were later degraded into light‐toned knobs that are rich in Fe/Mg‐phyllosilicates. On the rim of the Simois and the unnamed basins, a sequence of Al‐phyllosilicates on top of Fe/Mg‐phyllosilicates has been observed. These Al‐phyllosilicate‐rich materials may have been formed by pedogenic leaching. The presence of chloride in the area suggests that a playa environment prevailed during the last stage of water presence or after desiccation of the lakes. In the Early Amazonian, the last aqueous activity cemented the postlacustrine air fall deposits in the basins and shows that liquid water was present in Terra Sirenum long after the Noachian. Key Points: Reconstructing the Noachian‐Amazonian geological history of the Eridania basin Investigating the mineralogical composition of light‐toned materials Understanding the aqueous activity after the Noachian period